Nonlinear Transient Finite Element Analysis of Dog Bone Specimen - Yew, Weng Keong (IRC, 2018)

(untitled)
Pressure vessel has been widely used in the industry, it main function is to heat up the material to desired temperature, sequentially it may alter the material properties in produce other output. However, after consistent applied thermal load on the pressure vessel itself, it has the tendency to experience failure and require for support to minimize the lost. Due to the high expenditure where most of the company would like to avoid it, hence the demand of predicting life of pressure vessel using numerical modeling is certainly promising. This research paper aims to develop Finite Element Model of dog bone specimen using ANSYS APDL. Then second objective of investigate strain rate of selected specimen based on Ramberg Osgood. Stress strain rate of the uniaxial isotropic model is the most promising data to be study. This paper describes the problem as selecting suitable material model and element type to be used so that in future the simulated model can apply in probabilistic study. ANSYS will be used in examine the deformation of steel material by applying structural and thermal load in transient state. As for the expected outcome from this project, the model is justified and meet the requirement with simulation and experimental result from literature review. Ultimately, Ramberg Osgood model is capable in uniaxial isotropic testing as the stress strain curve −1 obtain is met. The strain rate of the tested dog bone specimen is 0.011414